Student Politics in Africa Representation and Activism - Otieno Jowi, James; Klemen{caron}ci{caron}c , Manja; Luescher, Thierry M.; Project Muse; Project Muse. (Project Muse, 2016)
The second volume of the African Higher Education Dynamics Series brings together the research of an international network of higher education scholars with interest in higher education and student politics in Africa. Most authors are early career academics who teach and conduct research in universities across the continent, and who came together for a research project and related workshops and a symposium on student representation in African higher education governance. The book includes theoretical chapters on student organising, student activism and representation; chapters on historical and current developments in student politics in Anglophone and Francophone Africa; and in-depth case studies on student representation and activism in a cross-section of universities and countries. The book provides a unique resource for academics, university leaders and student affairs professionals as well as student leaders and policy-makers in Africa and elsewhere.
Foreword -- 1. Introduction / Thierry M Luescher, Manja Klemen{caron}ci{caron}c and James Otieno Jowi -- 2. Student organising in African higher education : polity, politics and policies / Manja Klemen{caron}ci{caron}c, Thierry M Luescher and Taabo Mugume -- 3. Student representation in a context of democratisation and massification in Africa : analytical approaches, theoretical perspectives and #RhodesMustFall / Thierry M Luescher -- 4. The evolving nature of student participation in university governance in Africa : an overview of policies, trends and emerging issues / Ibrahim Oanda -- 5. The three ages of student politics in Francophone Africa : learning from the cases of Senegal and Burkina Faso / Pascal Bianchini -- 6. Revisiting student participation in higher education governance at the University of Buea, Cameroon : 2004-2013 / Samuel N Fongwa and Godlove N Chifon -- 7. Student participation in the governance of Ethiopian higher education institutions : the case of Addis Ababa University / Bekele Workie Ayele -- 8. Private higher education and student representation in Uganda : a comparative analysis of Makerere University and Uganda Christian University / Taabo Mugume and Mesharch W Katusiimeh -- 9. Student actions against paradoxical post-apartheid higher education policy in South Africa : the case of the University of the Western Cape / Mlungisi BG Cele, Thierry M Luescher and Teresa Barnes -- 10. The University of Burundi and student organisations : governance system, political development and student representation / G{acute}erard Birantamije -- 11. Politicisation of the National Union of Ghana Students and its effects on student representation / Ransford EV Gyampo, Emmanuel Debrah and Evans Aggrey-Darkoh -- 12. Conclusion / James Otieno Jowi -- Epilogue. Students, politics and universities : in search of interpretive schemes for the 21st century / Lis Lange.
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Student movements -- Africa; College students -- Africa -- Political activity; Electronic books; Electronic books